Board Game Pengenalan Pasukan Elite Kerajaan Majapahit - Ramadhan, Gilang; Iskandar, M Syahril (Fakultas Desain Universitas Komputer Indonesia, 2021)
The Majapahit Empire was a very succeeded empire in the 13th century, the Majapahit Empire was famous with best peoples on conquering a country, as evidenced by the invasion carried out by Majapahit by expanding territory to Vietnam. At time of the Empire, Majapahit had elite troops like the current KOPASSUS troops which became a feared force in Asia and in the world. The elite troops of the Majapahit Empire were called the Bhayangkara troops. The design of information in the introduction of the elite troops of the Majapahit Empire, that is Bhayangkara, uses an interesting and educational concept, because this design aims to provide information in a fun way to increase students interest in studying history. The visual style used is a cartoon drawing style so that the design is attractive to students and also inserts elements of history and tradition. The visual creations in this design take from several historical relics such as statue, reliefs, paintings, weapons, objects from the Majapahit Empire and the Mongols.